2000
DOI: 10.1097/00005392-200012000-00054
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Dysplastic Renal Moiety and Ectopic Ureter

Abstract: MRI may facilitate diagnosis, guide cystoscopy and aid in preoperative planning in children with poorly functioning renal moieties and ectopic ureters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…recommend B‐mode ultrasound and/or color Doppler imaging for preoperative localization, and Gylys‐Morin et al . suggested that MRI might help preoperative planning 7,8 . However, the rarity of single‐system ectopic ureter draining into a dysplastic kidney makes it difficult to generalize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recommend B‐mode ultrasound and/or color Doppler imaging for preoperative localization, and Gylys‐Morin et al . suggested that MRI might help preoperative planning 7,8 . However, the rarity of single‐system ectopic ureter draining into a dysplastic kidney makes it difficult to generalize.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al recommend B-mode ultrasound and/or color Doppler imaging for preoperative localization, and Gylys-Morin et al suggested that MRI might help preoperative planning. 7,8 However, the rarity of single-system ectopic ureter draining into a dysplastic kidney makes it difficult to generalize. Therefore, a proportion of cases are diagnosed by a high index of suspicion with precise history taking without radiologic confirmation of dysplastic kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible for infections causing oedema and fibrosis to aggravete the stenosis at the insertion site of the ureter to vagina. Magnetic resonance urography has been re-cently reported as a highly effective tool to detect poorly functioning dysplastic renal moieties and ectopic ureters [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Video-clip cine-loop documentation or m-mode US improves the comparison of peristalsis during follow-up and thus improves the detection of impairment or deterioration (i.e., increasing hyperperistalsis in the aggravation of stenosis, lack of peristalsis in adynamic-dysplastic megaureter segments or in ureteral exhaustion) (Riccabona et al 1998b ). In complex conditions (e.g., duplex kidney, ectopic insertion), MRU is the modality of choice for additional imaging of (preoperative) anatomic and -by additional delayed acquisitions -drainage details (Avni et al 1997(Avni et al , 2001(Avni et al , 2002Gylys-Morin et al 2000 ;Riccabona et al 2004a ). Only rarely -in infected systems that do not respond to intravenous antibiotic treatment or in bilateral obstruction with renal failure -percutaneous nephrostomy under US guidance needs to be performed (Riccabona et al 2002b , c ).…”
Section: Imaging Algorithm In Obstructive Uropathymentioning
confidence: 99%